AN ASSESSMENT OF PHYSICAL APTITUDE IN THE NETWORK OF PUBLIC SCHOOLS INVOLVED IN FUNDAMENTAL EDUCATION IN CAMPO GREANDE – MS (Fiep Bulletin - online, 2015)
This research will try to identify, if it is a common practice for the physical education teachers, to apply physical aptitude tests in the students of elementary education of public schools in Campo Grande, Mato Grosso do Sul, and if it happens, identify if the results have been used in the pedagogical plan of the physical education classes.  For this purpose, we chose the urban Bandeira area, that is under the administration of the Campo Grande City, where we can find 10 (ten) of the 94 (ninety four) municipal schools, what gave us the chance to apply for 33 physical education teachers, a socio-demographic questionnaire to identify the profile of sample with open and closed questions. The theory being clear, to produce and demonstrate the importance of physical aptitude for the development of the child, becoming a complete human being, and the evaluation ought be an important part of planning for all Physical Education teachers. Based on the information received from this heterogeneous group of teachers, we discovered that there is no consensus about the need of physical aptitude tests in students of fundamental studies in the network of public school in Campo Grande and, even when they are done, they are not applied in the planning of his classes.
Keywords: Physical assessment; Physical education; School